The Effect of Using Froggy Jump Game in Educaplay Media on Students’ Vocabulary Mastery - Rahmat Aditya Mahmud; Rasuna Talib; Moh. Syahrun Ibrahim; Karmila Machmud; Titien Fatmawaty Mohammad (Universitas Islam Negeri Palopo, 2026)
Vocabulary mastery is a foundational element of English language acquisition, yet many learners continue to struggle with it in classroom settings. This study explored how the Froggy Jump game, accessed through Educaplay media, affected vocabulary mastery among seventh-grade students at SMP Negeri 1 Botupingge. A quantitative approach was employed using a one-group pre-test and post-test design. Twenty-eight students from class 7A were selected as the sample through purposive sampling from a population of 246 students across three grade levels. The intervention was conducted over six meetings, with a vocabulary test administered before and after the treatment to measure learning gains. A significant difference between pre-test and post-test scores was established through paired-sample t-test analysis, which returned a p-value of 0.000, considerably lower than the 0.05 significance threshold. The mean score improved markedly from 45.57 to 85.57, demonstrating a substantial gain in vocabulary mastery. These findings confirm that the use of the Froggy Jump game had a positive and meaningful effect on students' vocabulary learning outcomes. The findings of this study strengthen existing scholarly evidence regarding the effectiveness of game-based digital media in EFL instruction, while also offering actionable implications for language educators seeking to enhance student engagement and vocabulary acquisition through technology-integrated learning.